“Fresh vs dry grafting in interlay type-1 tympanoplasty” - Bhagirathsinh D. Parmar; Krupal J. Joshi; Dharmendra Solanki (The Egyptian Journal of Otolaryngology)
Abstract Background Chronic otitis media is a common middle ear disease that leads to varying degrees of hearing loss and otorrhoea. Tympanoplasty is a common surgery used for the reconstruction of sound conductive pathways in mucosal-type COM. Aims The study aims to compare the fresh and the dry grafting technique in interlay type-1 tympanoplasty amongst the patients of inactive mucosal type chronic otitis media. Objectives The objectives of the study are to compare graft uptake rate, pre-op and post-op AB gap, residual hearing loss, and average graft epithelialization time between the fresh and the dry grafting technique in interlay type-1 tympanoplasty. Methods A retrospective cohort study of 48 patients of COM inactive mucosal-type who underwent interlay type-1 tympanoplasty between July 2020 and March 2022. Results Out of 48 patients, in 23 patients, the fresh graft was used, while in the rest 25 patients, the dry graft was used. The overall (fresh + dry group) graft uptake rate at the end of three months was 97.9%. The graft uptake rate was 100% with the use of the fresh graft and 96% with the use of the dry graft. The pre-op average air-bone (AB) gap was 12.21 ± 4.23 dB in patients where the fresh graft was used and in patients where the dry graft was used. An overall pre-op average AB gap was 13.35 ± 3.81 dB. The average time for epithelialization was 24.43 ± 4.17 days with the use of the fresh graft and 49.75 ± 6.93 days with the use of the dry graft. It was also statistically significant with a P-value of 0.001. Conclusions The fresh graft in the interlay type-1 tympanoplasty shows higher graft uptake rates, reduced epithelialization time, and better hearing improvement compared to dry graft. However, different complication rates are similar with the use of both types of grafts.